Development a deeper understanding of visitors' sentiments towards natura 2000 protected areas: Evidence from online reviews - Kosmas, Petros C.; Theocharous, Antonis L.; Christodoulou, Evripides; Andreev, Hristo; Giannoulis, Petros; Panagopoulou, Maria (My University, 2024)
User-generated data shared by visitors on TripAdvisor provide opportunities to understand how people perceive the Natura 2000 protected areas during nature-based recreational experiences. In this study, we propose to deploy natural language processing and topic modelling technique to identify important aspects and insights of visitors using their electronic word-of-mouth (e-WOM) feedback. For the purpose of identifying the pros and cons of visitor experience, pre-existing rating systems have been utilized resulting in a conceptualization of the visitor experience in Akamas Peninsula Natura 2000 site of Cyprus. The findings of this empirical research can provide solutions into how protected areas and national parks are perceived and constructed in the virtual social environment. By implementing this proposed method, socio-political support for preservation can be enhanced, as well as environmental management plans can be improved to ensure biodiversity is protected. Additionally, it can contribute to the provision of essential goods and services for human well-being through sustainable and responsible tourism strategies that promote the sustainability of protected areas and the preservation of natural heritage.
Keywords: Online reviews; Protected areas; NATURA 2000; Sentiment analysis; Topic analysis; XGBoost; e-WOM; Clustering algorithm; TripAdvisor platform; Social environment; Akamas Peninsula; Cyprus